Mechanical analysis of bamboo and agro-industrial residue one-layer particleboard - Nasser, Sílvia M. [UNESP]; Morales, Elen A. M. [UNESP]; Pereira, Luiz E. R. [UNESP]; Eugenio, Rafael A. P. [UNESP]; Biazzon, João C. [UNESP]; Lima, Mauri P. [UNESP]; Bueno, Marcus A. P. [UNESP]; Archangelo, Andreia [UNESP]; Celestino, Valter R. B. [UNESP]; Nasser, Hanilton M. [UNESP]; Dias, Larissa G. [UNESP]; Munhoz, Marcelo R. [UNESP]; et al. (BioResources, 2020)
A high-density particleboard composed of peanut shells (Arachis hypogaea L.), an agro-industrial residue, and bamboo wastes of the species Dendrocalamus giganteus (branches and apical part), bonded with a two-component polyurethane resin based on castor oil (Ricinus communis L.) in the proportion of 12% of the particleboard mass, was produced. Four types of specimens were prepared according to the percentage of peanut shells: 0%, 10%, 20%, and 30%. Mechanical characteristics were evaluated through the flexural strength tests for modulus of rupture, modulus of elasticity, perpendicular traction, and screw pull resistance. The particleboard reached an average density of 917.2 kg/m3, meaning that it could be classified as high-density particleboard. The results of the mechanical tests indicated that the specimens containing a mixture in the proportion of 90% bamboo and 10% peanut hull presented the best mechanical strength. The experiment produced particleboards with a satisfactory mechanical physical performance that met the standards ABNT NBR 14.810-2 and ANSI A208-1, supporting the use of the peanut shell residue in the manufacture of particleboards to be used in internal environments and allowing the applicability of this residue through additional value.
Keywords: Agro-industrial waste; Bamboo; Mechanical strength; Particleboards; Sustainability